Avaliação de ferramentas na furação de laminados compósitos - D. J. S. Goncalves (2011)
The development of cutting tools becomes a challenge to the industry of composite materials to obtain high quality holes, minimizing damage. This work aims to examine the influence of various parameters such as feed rate and tool geometry on thrust forces developed during drilling operations and on the extent of damage.In this work, a comparative study of tool geometry with the aim of reducing the associated damage during drilling process is presented. In the end a good combination of tool geometry and drilling parameters based on experimental work will be presented.